Postmodernisme: Katalis Transformasi Sosial: Postmodernism: Catalyst of Social Transformation - Muthohar, Muhammad Amin; Sholeh, Achmad Khudori (Jurnal Filsafat Indonesia, 2025)
The study of postmodernism is very important to discuss because it considers that truth is relative and subjective. This causes instability in society, one of which is social transformation. This article aims to describe the concept of postmodernism, the concept of social transformation and analyze the implications of postmodernism for social transformation. This research is in the form of library science research or literature using qualitative methods. The research process begins with researching, observing and recording various ideas, concepts, and information from various postmodernism publications. The results of this study are : first, Postmodernism is divided into several forms, namely extreme postmodernism, moderate postmodernism and theoretical postmodernism. In addition, postmodernism has several principles including spiritualism, relativism, pluralism and deconstruction. Second, the social transformation can be in the form of changes in mindset, changes in behavior, and cultural changes. Furthermore, Third, the influence of postmodernism on social transformation includes relativism of truth which is defined as an attitude to state that truth is relative and depends on a particular context, view, or situation. Identity fragmentation is defined as an attitude that refers to the separation or division of aspects of individual identity, especially in cultural and social contexts. Decentralization of culture means the spread of a culture from the center to all corners of society. Therefore, postmodernism can have both positive and negative implications for social transformation depending on the approach chosen.